Pengaruh Pengetahuan Kewirausahaan, Program Studi dan Gender terhadap Minat Beriwirausaha Mahasiswa - Robiatul Adawiyah; Efrita Norman; Dedi Junaedi (LPPM Institut Nasional Laa Roiba Bogor, 2020)
ABSTRACT Unemployment and a weak entrepreneurial spirit are serious problems in Indonesia. This study aims to determine the effect of entrepreneurial knowledge, study program, semester level and gender on interest in entrepreneurship among FEBI INAIS students. The method used is a quantitative study with multiple regression analysis of dummy variables. The research sample was 133 FEBI INAIS students. The results showed: there was a positive and significant influence on entrepreneurial knowledge, a positive and significant influence on entrepreneurial knowledge, study programs, semester level, and gender on interest in entrepreneurship in FEBI INAIS students. Keywords: entrepreneurship, gender, department, interest, knowledge,